Developing Ethical Practices for Public Health Research Data Sharing in South Africa: The Views and Experiences From a Diverse Sample of Research Stakeholders. (July 2015) - Denny, Spencer G.; Silaigwana, Blessing; Wassenaar, Douglas; Bull, Susan; Parker, Michael
The abundance of South African clinical and public health research data has the potential to unlock important and valuable future advances in biomedical science. Amid increasing calls for more effective sharing of individual-level data, commitment to promote access to research data is evident within South Africa's public research sector, but national guidance and regulation are absent. This qualitative study examined the perceptions, experiences and concerns of 32 research stakeholders about data-sharing practices. There was consensus about the utility of data sharing in publicly funded health research. However, disparate views emerged about the possible harms and benefits of sharing data and how these should be weighed. The relative dearth of policies governing data-sharing practices needs to be addressed and a framework of support developed that incentivizes data-sharing practices for researchers that are both ethical and effective.